Venturi Meter Gas Flow Calculations - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2018)
Venturi meters are widely used for flow measurement of gases in pipes. An iterative calculation is needed to determine the required throat diameter for specified flow rate, pressure drop across the meter, and pipe diameter. Also, a value is needed for the venturi coefficient to make any type of venturi meter calculations. This workbook has worksheets for calculating: i) flow rate for specified pipe diameter, throat diameter, and pressure drop across the meter ii) required throat diameter for specified flow rate, pipe diameter and pressure drop across the meter iii) pressure drop across the meter for specified flow rate, pipe diameter and throat diameter Each of these calculations can be made using a venturi coefficient value from ISO 5167-4-2300 if the venturi meter is one of three ISO 5167 standard venturi meter types, or they can be made with a user specified value for the venturi coefficient. There is also a worksheet that allows the user to determine the needed gas properties for any of 21 common gases.